Towards improving magnetic resonance image classification - Trojachanec, Katarina; Madzarov, Gjorgji; Loshkovska, Suzana (My University, 2010)
The main goal of this paper is to propose and investigate a three-stage hierarchical classification scheme. The proposed scheme was examined on the dataset of magnetic resonance images. The experimental results obtained from the classification with the proposed method outperformed the results provided by the flat classification and the two-stage hierarchical classification examined in our previous work. According to this, we can conclude that the proposed method is more suitable for solving MRI classification problem.
Keywords: Magnetic Resonance Imaging (MRI), feature extraction, image classification, hierarchical classification